Culture's Place in Quality of Care in a Resource Constrained Health System: Comparison Between Three Malawi Districts - Patterson, Patrick B; Zubia, Mumtaz; Chirwa, Ellen; Mambulasa, Janet; Kachale, Fannie; Nyagero, Josephat (Qualitative Health Research, 2021)
Public health scholars describe "culture of quality" in terms of desired values, attitudes, and practices, but this literature rarely includes explicitly stated theories of culture formation. In this article, we apply Fredrik Barth's transactional model to demonstrate how taking a theory-centered approach can help to identify what would be necessary to foster "cultures of quality" outlined in the public health literature. We draw on data from a study of the Republic of Malawi's Performance and Quality Improvement for Reproductive Health initiative. These data were generated in 2017-2018 through a 6-month organizational ethnography in three facilities selected to represent a range of districts with differing social and economic contexts. Our analysis revealed facility-level organizational cultures in which staff valued providing care, but responded to structural constraints by normalizing divergence from quality-of-care protocols. These findings indicate that sustaining a quality-oriented organizational culture requires addressing underlying conditions that generate routine experiences and practices.
Keywords: Malawi; Organizational ethnography; Care provision; Organizational culture; Quality improvement.